The Impact of Fuel Subsidy to the Income Distribution: The Case of Indonesia - Anggito Abimanyu; Muhammad Handry Imansyah (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
This paper aims to examine the potential impact of energy subsidies (fuel and liquified petroleum gas or LPG)) on income distribution in Indonesia. Indonesia suffers from the high price of crude oil resulting in an increase in fuel subsidies from imports of crude oil. The impact of fuel subsidies has the potential to favor urban and high-income groups. This form of price subsidy has a weakness because all income groups can buy subsidized fuel and LPG. Therefore, in terms of fairness, this type of subsidy is not justified. The method of measuring the effect to income groups benefited from price subsidies used in this study is Miyazawa's input-output analysis. The study finds that the lower-income groups receive less benefits than the higher-income groups, and even the top decile earns the highest income. This study provides several reform examples conducted by some developing countries in overcoming the negative impacts of fuel subsidy policies that are politically and economically relevant to the conditions in Indonesia. To reduce the negative impacts of fuel price subsidies, the study suggests several policy initiatives that need attention from the government. These include the automatic subsidy price adjustment law, implementing a sustainable fuel subsidy social program, improving data quality and implementing a separate PSO (public sector obligation) policy.